2012
DOI: 10.1590/s0104-66322012000300008
|View full text |Cite
|
Sign up to set email alerts
|

Second law analysis for free convection in non-newtonian fluids over a horizontal plate embedded in a porous medium: (prescribed heat flux)

Abstract: -Second law characteristics of heat transfer and fluid flow due to free convection of non-Newtonian fluids over a horizontal plate with prescribed surface heat flux in a porous medium are analyzed. Velocity and temperature fields are obtained numerically using an implicit finite difference method under the similarity assumption and these results are used to compute the entropy generation rate Ns, irreversibility ratio ϕ and the Bejan number Be for both Newtonian and non-Newtonian fluids. The effects of power-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(4 reference statements)
0
3
0
Order By: Relevance
“… 10 , Qasim 11 and Noor 12 . Also, of considerable interest for the present paper are the book by Bejan 13 , and the papers by Bejan 14 , and Khan and Gorla 15 . It should also be mentioned that the Bejan number was highlighted as a useful number for the topic of entropy generation analysis for non-Newtonian fluid (see Yazdi et al .…”
mentioning
confidence: 92%
“… 10 , Qasim 11 and Noor 12 . Also, of considerable interest for the present paper are the book by Bejan 13 , and the papers by Bejan 14 , and Khan and Gorla 15 . It should also be mentioned that the Bejan number was highlighted as a useful number for the topic of entropy generation analysis for non-Newtonian fluid (see Yazdi et al .…”
mentioning
confidence: 92%
“…Bejan proposed entropy generation minimization (EGM) method to determine the optimal system design characteristics [14,15], and serves as an effective approach. Khan and Gorla [16] analyzed the exergetic features of heat transfer and fluid flow of natural convection with non-Newtonian fluids over a horizontal plate of a given surface in a porous medium. Oliveski et al [17] presented a numerical analysis on entropy generation of natural convection in rectangular cavities, where results indicated that the total entropy generation in steady state increase linearly with the aspect ratio and the irreversibility coefficient, and exponentially with the Rayleigh number.…”
Section: Introductionmentioning
confidence: 99%
“…Zehtabiyan-Rezaie et al (2017) performed a numerical study of heat transfer enhancement and entropy generation in the flow inside open cavities in the presence of inclined magnetic fields. Khan and Gorla (2012) presented the second law analysis of heat transfer and fluid flow due to free convection over a horizontal plate with prescribed surface heat flux. Shuja et al (2008) studied flow over a porous block inside a channel and numerically studied the effects of channel inlet port height, porosity, and block aspect ratio on entropy generation.…”
Section: Introductionmentioning
confidence: 99%